Oral health behaviour among adolescents in Kerala, India (Italian Journal of Public Health, 2009)
Background: Oral health behaviour is essential for planning & evaluation of oral health promotionprogrammes. This study was conducted to assess the oral health behaviour among adolescents agedbetween 11 to 19 years in Kannur district, Kerala state in India, including their inter-dental cleaning habits.Methods: 512 school children aged 11 to 1 9 years, studying from 6th to 12th standards formed the studysubjects.Results: 52.5% were females and remaining were males. 40.8% were Hindus. Brushing of teeth twice dailywas practiced by 75% of students. A significant association was found between the correct brushingtechnique and male gender as well as students in upper primary school compared to high school and highersecondary school education level. The prevalence of inter-dental cleaning habit was observed to be 58%.76.3% of males and 58.9% of females used coconut leaf toothpicks for inter-dental cleaning. Multivariateanalysis revealed age, religion and positive attitude towards inter-dental cleaning as significant factorsassociated with the practice of inter-dental cleaning.Conclusions: There was a statistically significant association between gender, age, class of study andrecommended method of tooth brushing. More than half of the study subjects practiced inter-dental cleaningand the materials used were locally and easily available those are not recommended by oral healthprofessionals. Multivariate analysis shows age, religion and attitude were the factors significantly associatedwith regular practice of inter-dental cleaning. Oral health professionals can plan, propose and implementschool oral health promotion activities as part of building up oral health promoting school.
Keywords: adolescent; behaviour; health promotion; inter-dental cleaning; oral hygiene